EFFECT OF ADDING DIFFERENT LEVELS OF B-MANNANASE TO BROILER RATIONS CONTAINING HIGH WHEAT LEVEL ON SOME PRODUCTIVE PERFORMANCE OF THE BIRDS - H . A . Al – Mashhadani; N . S . Al – Rubaie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was conducted at the poultry farm of Animal Production Department - College of Agriculture - University of Baghdad, for the period from 18/9/2016 t0 30/10/2016. The aim of this experiment was to investigate the effect of adding different levels of β-Mannanase (0، 0,025 ، 0,05 ، 0,075، 0,1، 0,125%) to the diets on productive traits of broiler chickens, A total of 450 unsexed Ross 308, one day old was used in this experiment. chicks were fed on starter for 1_ 10 diet the day of age and on Grower diet for 11_ 24 the days of age the birds and finisher diet for 25 _ 42 days of the birds age, Birds were distributed on six treatments: T 1 as control group (without any addition) however T2, T3, T4, T5, and T6, were supplemented with β_Mannanase in the diet concentrations (0، 0,025 ،0,05، 0,075، 0,1، 0,125%) respectively, The results indicated that the addition of β_Mannanase in the diet which concentration (0.05 %) (T3) led to significant improvement in live body weight and average body weight gain of the birds.